ECOFRIENDLY TREATMENTS AND DROUGHT CONDITIONS AS A TOOL FOR THE INDUCTION OF MEDICINALLY ACTIVE COMPOUNDS ON POTATOES. - Zainab J. Al-Mousawi,; I. J. Abdul Rasool,; Aseel M.H. H. Al-Khafaji,; F. Y. Baktash,; K. D. H. Al-jubouri, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This experiment aimed to improve the qualitative traits and stimulate the accumulation of antioxidants  in potato plants under environmentally sustainable agricultural practices. A field experiment was conducted during the spring season of 2023 at the fields of the College of Agricultural Engineering Sciences, University of Baghdad, using a Randomized Complete Block Design (RCBD) within  split-plot arrangement with two factors and three replications (2 × 6 × 3). The first factor involved the application of titanium dioxide nanoparticles (TiO₂-NPs) at concentrations of 0 and 10 ml·L⁻¹, denoted as (T₀) and (T₁), respectively. The second factor included six treatments as follows: natural irrigation (I), prolonged irrigation (D), biofertilizers under prolonged irrigation (DB), biofertilizers under prolonged irrigation with mannitol (DBM), biofertilizers under prolonged irrigation with xanthan gum (DBZ), and biofertilizers under prolonged irrigation with both mannitol and xanthan gum (DBMZ). The results showed that foliar application of TiO₂-NPs (T₁) led to significant improvements in most of the studied traits. Moreover, the interaction treatment (T₁DBMZ) recorded the highest qualitative and antioxidant traits compared to the prolonged irrigation treatment without any additions (T₀D).